Analisis Karakteristik Nilai Religius Dan Makna Spiritual Pada Novel Negeri 5 Menara - Aida Fitri Puspitasari; Fajarotul Nur Isnaini; Renie Ria Rusmawati (Jurnal Ilmu Pendidikan, 2025)
This study examines religious values and spiritual meaning in the novel Negeri 5 Menara by Ahmad Fuadi. The story portrays life in a pesantren, highlighting Islamic values such as the spirit of learning, prayer, and faith in Allah's will. Using a qualitative approach, the study analyzes religious elements in the plot, characters, and conflicts. It also explores the spiritual motivations driving the characters to achieve their goals, guided by the principle "Man Jadda Wajada" (those who strive will succeed). The findings reveal that the novel's religious values not only strengthen the characters' faith but also inspire readers to lead more meaningful lives. This novel stands as an important work in conveying moral and spiritual values.